Early Universal Screening with a Combination of Fasting Plasma Glucose and Glycated Haemoglobin is the Best Community Screening Strategy for Dysglycaemia in Indian Youth - Abilash Nair; Jabbar P. Khadar; Jayakumari Chellama; Alpesh Goyal; Sriharii Sivakumar; Tanvir K. Gandhi; Bipin K. Gopal; Joy John; Giri Vishnu; Anish T. Surendran Nair; Amal Kingsley; Chintha Sujatha; et al. (Indian Journal of Endocrinology and Metabolism)
Introduction: Any intervention to reduce the incidence of diabetes needs to target the young population at the stage of early insulin resistance or prediabetes. There are no screening guidelines for dysglycaemia in non-obese youth. This study was designed to find the best screening investigation for dysglycaemia in community-dwelling youth. Methods: Using multistage sampling, community-dwelling non-obese subjects aged 18–30 years were assessed for diabetes using a 75 g oral glucose tolerance test [OGTT], fasting plasma glucose [FPG] and glycated haemoglobin (HbA1c) at a health facility near the participants’ home. Diagnosis of dysglycaemia (diabetes and prediabetes) was made based on the American Diabetes Association (ADA) criteria. Results: A total of 2540 participants from 74 family welfare centres with a mean age of 24.2 ± 3.5 years and 1292 female (50.8%) participants were included. Urban, rural, coastal and hilly regions contributed 661 (26%), 580 (22.8%), 656 (25.8%) and 643 (25.3%) participants, respectively, and 88.4% of participants came from the middle or lower middle class. Diabetes was detected in 59 (2.3%) and prediabetes in 568 (22.4%) of these young participants. The sensitivity of HbA1c with FPG in diagnosing diabetes mellitus (DM) and prediabetes was 87.87%, whereas the sensitivity of FPG and 2-h OGTT together was 44.2% (P < 0.001). Conclusion: The prevalence of dysglycaemia in non-obese Indian youth is alarmingly high. There is an urgent need to define screening strategies for dysglycaemia in this population. Based on this study, universal screening for dysglycaemia using HbA1c and FPG in early adulthood is recommended.